Gambaran Tingkat Pengetahuan Masyarakat tentang Pencegahan Diabetes Melitus Tipe 2 di Puskesmas Perawatan Siko - Fatmona, Fikri Ardiansyah; Permana, Dini Rahmawati; Sakurawati, Andi (Universitas Malahayati, 2023)
ABSTRACT Diabetes mellitus (DM) is defined as a chronic and multietiological disease or metabolic disorder of the body characterized by increased levels of sugar in the blood due to the inability of insulin to perform its functions. The numbers of DM keep increasing day by day from 2013 (6.9%) to 2018 (10.9%). The incidence of DM in Ternate City in 2021 was 2975 cases in all age groups with 54 deaths. The study aims to describe the level of public knowledge about the prevention of Type 2 Diabetes Mellitus at the Siko Health Care Treatment. This type of research is an observational descriptive study with a cross-sectional approach. This research was carried out at the Siko Care Health Center, North Ternate District, which was carried out from May to June 2023. The determination of the minimum sample in this study uses the Slovin formula so that a minimum sample size of 100 people is obtained. The data used in this study are primiary data in the form of questionnares and secondary data in the form of number of residents and the number of cases of DM in the work area of the Siko Care Health Center. The data obtained will be through editing, scoring, coding and tabulating using SPSS. Results from 100 populations, with the highest percentage at the age of 25-34 years as many as 33 respondents (33.0%), sex with the highest percentage in women as many as 6 respondents (76.0%), education with the highest percentage in high school as many as 52 respondents (52.0%), the highest percentage in IRT as many as 38 respondents (38.0%), and based on the level of knowledge with the highest percentage of good knowledge as many as 85 respondents (85.0%). In this study it was concluded that the distribution of people in the Siko Public Health Center regarding knowledge of Type 2 DM was in the good category and based on the level of knowledge with the highest percentage of good knowledge as many as 85 respondents (85.0%). Keywords: Knowledge, Prevention, Siko Health Center, Type 2 DM ABSTRAK Diabetes melitus (DM) diartikan sebagai penyakit atau gangguan metabolisme tubuh yang kronis dan multietiologi yang ditandai dengan peningkatan kadar gula dalam darah akibat dari tidak mampunya insulin dalam melakukan fungsinya. Jumlah kasus DM terus meningkat dari tahun ke tahun pada tahun 2013 (6.9%) hingga pada tahun 2018 (10.9%). Angka kejadian DM di Ternate pada tahun 2021 berjumlah 2975 kasus dalam semua kelompok usia dengan angka kematian berjumlah 54 orang. Penelitian ini bertujuan untuk mendeskripsikan gambaran tingkat pengetahuan masyarakat tentang pencegahan Diabetes Mellitus Tipe 2 di Puskesmas Perawatan Siko. Jenis penelitian ini adalah penelitian deskriptif observasional dengan pendekatan cross-sectional. Penelitian ini dilaksanakan di Puskesmas Perawatan Siko, Kecamatan Ternate Utara yang dilaksanakan pada bulan Mei hingga Juni 2023. Penentuan minimal sampel dalam penelitian ini menggunakan rumus slovin sehingga didapatkan besar minimal sampel sebesar 100 orang. Data yang digunakan dalam penelitian ini adalah data primer dalam bentuk kuesioner dan data sekunder dalam bentuk jumlah penduduk serta jumlah kasus DM di wilayah kerja Puskesmas Perawatan Siko. Data yang didapatkan akan melalui editing, scoring, coding dan tabulating menggunakan SPSS. Hasil dari 100 populasi, dengan persentase tertinggi pada usia 25-34 tahun sebanyak 33 responden (33.0%), jenis kelamin dengan persentase tertinggi pada perempuan sebanyak 76 responden (76.0%), pendidikan dengan persentase tertinggi pada SMA sebanyak 52 responden (52.0%), persentase tertinggi pada IRT sebanyak 38 responden (38.0%), dan berdasarkan tingkat pengetahuan dengan persentase tertinggi pada pengetahuan baik sebanyak 85 responden (85.0%). Pada penelitian ini disimpulkan bahwa mayoritas masyarakat di Puskesmas Siko memiliki tingkat pengetahuan kategori baik persentase pengetahuan baik tertinggi sebanyak 85 responden (85,0%). Kata Kunci: Pengetahuan, Pencegahan, Puskesmas Siko, DM Tipe 2